LEGAL REFORMULATION OF LEGISLATIVE ELECTIONS IN REALIZING PANCASILA DEMOCRACY IN INDONESIA - Sistyawan, Dwanda Julisa (Jurnal Hukum Progresif, 2024)
This research aims to analyze and reformulate the legislative election law in Indonesia to realize Pancasila democracy. The study suggests three key reformulation strategies: revising the Parliamentary Threshold to uphold popular sovereignty, improving the financial governance of political parties to combat corruption and money politics, and enhancing the accountability of political parties. By aligning with Pancasila principles, these reforms aim to strengthen the electoral system and uphold democratic values. The study emphasizes the importance of legal measures that do not violate the Constitution while empowering lawmakers to establish transparent electoral rules. Ultimately, the research advocates for legal reforms that promote fair elections, combat corruption and ensure accountability within political parties to uphold the ideals of popular sovereignty and democracy in Indonesia.